2021
DOI: 10.1080/14740338.2021.1933429
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and practice of healthcare professionals following implementation of a Pregnancy Prevention Program for sodium valproate in Ireland: a multi-stakeholder cross-sectional study

Abstract: As a GP, you have a role in supporting implementation of prevent in cases where you have a patient that is a female child or WCBP, and to whom you provide repeat Epilim prescriptions. The following is a summary of the key actions for which you are responsible:3 Check the patient has a copy of the patient guide and that you have a copy of an up-to-date signed Annual Risk Acknowledgement Form each time a repeat prescription is issued 3 Unless there are compelling reasons to indicate that there is no risk of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The decline among 16–24 year olds in our study may indicate that the 2014 intervention reduced first‐time prescribing of valproate among neurologists in Ireland. These patterns observed, support our recent survey study findings from the Irish HCP setting, which found that all responding neurologists reported that they had considered an alternative treatment before initiating their patient on valproate 29 . In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention 30 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The decline among 16–24 year olds in our study may indicate that the 2014 intervention reduced first‐time prescribing of valproate among neurologists in Ireland. These patterns observed, support our recent survey study findings from the Irish HCP setting, which found that all responding neurologists reported that they had considered an alternative treatment before initiating their patient on valproate 29 . In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention 30 .…”
Section: Discussionsupporting
confidence: 88%
“…These patterns observed, support our recent survey study findings from the Irish HCP setting, which found that all responding neurologists reported that they had considered an alternative treatment before initiating their patient on valproate. 29 In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention. 30 Similarly, our study identified an overall decline in the month-to-month use of valproate among WCBP (16-44 years) following the 2014 EMA intervention.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…A cross‐sectional anonymous survey study was conducted that aimed to examine the effectiveness of risk minimisation measures in preventing harm from teratogenic medicines within an Irish healthcare setting. Further information on the study design and methods is previously described 14 . Briefly, the overarching survey design was adapted for the 2018 isotretinoin PPP, which outlines specific actions for prescribers and pharmacists to minimise the risk of exposure to isotretinoin during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…While obstetricians and gynecologists are less likely to prescribe isotretinoin, they may be involved in the care of women of childbearing potential (WCBP) who use retinoids, and they were recipients of the 2018 “Direct Healthcare Professional Communication” (DHPC) and educational materials. The participating HCPs were identified via their respective professional representative or regulatory body as outlined previously 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation